2020
DOI: 10.1177/1524839920954164
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Effectiveness of Reminders to Promote Colorectal Cancer Screening Uptake in Rural Federally Qualified Health Centers in West Virginia

Abstract: The purpose of this study is to evaluate the effectiveness of the West Virginia Program to Increase Colorectal Cancer Screening in implementing patient reminders to increase fecal immunochemical test (FIT) kit return rates in nine federally qualified health centers (FQHCs). Using process measures and cost data collected, the authors examined the differences in the intensity of the phone calls across FQHCs and compared them with the return rates achieved. They also reported the cost per kit successfully returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…This study demonstrated that modest financial incentives, together with patient navigation and patient reminders, can increase FIT kit return rates among a vulnerable rural, largely homeless population. The incremental cost per person screened was also estimated to be within the parameters found in our previous studies (Conn et al, 2020;Kim et al, 2020). The results supplement recommendations of The Community Guide, which recommends multicomponent, evidence-based interventions to promote CRC screening as a key strategy for eliminating disparities in cancer prevention and control (Community Preventive Services Task Force, 2012;Sabatino et al, 2012).…”
Section: Policy and Researchsupporting
confidence: 70%
See 2 more Smart Citations
“…This study demonstrated that modest financial incentives, together with patient navigation and patient reminders, can increase FIT kit return rates among a vulnerable rural, largely homeless population. The incremental cost per person screened was also estimated to be within the parameters found in our previous studies (Conn et al, 2020;Kim et al, 2020). The results supplement recommendations of The Community Guide, which recommends multicomponent, evidence-based interventions to promote CRC screening as a key strategy for eliminating disparities in cancer prevention and control (Community Preventive Services Task Force, 2012;Sabatino et al, 2012).…”
Section: Policy and Researchsupporting
confidence: 70%
“…As noted, the incremental cost was approximately $128 per additional screen at LFC. Our previous research in other settings has shown a wide range of incremental costs per additional CRC screen (Conn et al, 2020;Kim et al, 2020). In rural health centers in West Virginia that were implementing a multicomponent intervention (patient and provider reminders with patient assessment and feedback), we found the average cost per FIT kit returned to be approximately $60 (Conn et al, 2020).…”
Section: > > Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…During the study period, from July 2015 to December 2017, all health centers, except for one, experienced an increase in FIT kit return rates. In prior analyses, our team reported a wide range in the percentage of FIT kit returns at health centers from 31.0% to 81.6% (Conn et al, 2020;Kemper et al, 2018); the percentage of FIT kit returns in Neighborhood Healthcare centers was definitely on the high end of this range with percentages from 72.4% to 88.5% during the 6 months from July to December 2017. The percentage of FIT kit returns was already quite high, 75.1%, before the incentive program, which could be a result of the multicomponent interventions already implemented in the clinics.…”
Section: > > Discussionmentioning
confidence: 91%
“…West Virginia University worked with its FQHC partners to implement provider assessment and feedback in addition to at least one other EBI. We focused on sites that added patient reminders to increase FIT kit return rates (Conn et al, 2020). The University of Chicago and Heartland Health Centers in Chicago implemented a provider reminder system based on the electronic medical records but input manually.…”
Section: > > Interventions Crccp Awardees and Partner Clinicsmentioning
confidence: 99%